Effects of parenteral gibberellic acid and dietary supplementaion of vitamin D3 on egg quality and physiological characteristics in aged laying hens - Razuki, Waleed M.; Ibrahim, Dhia K.; Ali, Hala Ah. M. (Journal of Advanced Veterinary and Animal Research, 2014)
The aim of this study was to determine the effect of parenteral gibberellic acid (GA3) and/or vitamin D3 supplementation in diet on egg quality and blood physiological characteristics in aged laying hens. A total of 270 Lohmann Brown Classic laying hens aging 73-week were randomly assigned to equal three treatment groups (T1, T2 and T3) with equal 3 replicas in each group. The birds of group T1 (control group) were injected subcutaneously (SC) with sesame oil at 0.2 mL/kg body weight. The birds of group T2 were given with GA3 at 400 ?g/kg b.wt., SC, whereas group T3 had diet containing vitamin D3 at 500 IU/kg feed. Relative weight of albumen and egg shell, Haugh unit, shell thickness, serum glucose, serum calcium, serum phosphorous, serum estradiol, and bone calcium absorption were significantly increased in the birds of group T2 and T3. On the other hand, relative weight of yolk, yolk cholesterol, and serum cholesterol were significantly decreased in group T2 and T3 as compared to group T1. However, serum protein and albumen were unaffected in the treatments. In conclusion, the parenteral GA3 and vitamin D3 supplementation in diet could improve egg quality traits and serum blood biochemical perperties in agend laying hens. http://dx.doi.org/10.5455/javar.2014.a39